2012
DOI: 10.1111/j.1472-8206.2012.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilator and antihypertensive effects of a novel N‐acylhydrazone derivative mediated by the inhibition of L‐type Ca2+ channels

Abstract: New bioactive N-acylhydrazone derivatives synthesized from safrole previously have been found to promote intense vasodilation and antihypertensive activity. In this study, we describe the synthesis and the cardiovascular effects of the new N-acylhydrazone derivative (E)-N-methyl-N'-(thiophen-3-ylmethylene)benzo[d][1,3]dioxole-5-carbohydrazide (LASSBio-1289). Thoracic aorta and left papillary muscles from Wistar-Kyoto (WKY) rats and spontaneously hypertensive rats (SHR) were prepared for isometric tension recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…[36][37][38][39] To test our hypothesis, we performed vascular functional studies as well as experiments to identify the molecular mechanisms involved. Animals and Experimental Design Male SHR and control WKY were obtained at the age of 4 weeks (Hoshino Laboratory Animals, Inc., Ibaraki, Japan).…”
mentioning
confidence: 99%
“…[36][37][38][39] To test our hypothesis, we performed vascular functional studies as well as experiments to identify the molecular mechanisms involved. Animals and Experimental Design Male SHR and control WKY were obtained at the age of 4 weeks (Hoshino Laboratory Animals, Inc., Ibaraki, Japan).…”
mentioning
confidence: 99%
“…Then as we all know, high K + -induced (80mM) contraction in endothelium-denuded aortic rings is due to cell membrane depolarization and activation of the voltage-dependent Ca 2+ channel, especially for L-type Ca 2+ channel which could promote Ca 2+ influx[ 16 , 17 ]. According to our present study, both compound 1 and nifedipine can inhibit high K + -induced contraction in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] After the planning and synthesis of LASSBio-1289, its cardiovascular properties were evaluated. Pereira et al 20 demonstrated that LASSBio-1289 induces both endothelium-independent vasorelaxation involving the inhibition of Ca 2+ influx through L-type Ca 2+ channels in aorta from Wistar-Kyoto (WKY) and spontaneously hypertensive rats (SHR), as well as endotheliumdependent relaxation mediated by the nitric oxide/cyclic GMP (Guanosine Monophosphate) pathway in WKY rats.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, LASSBio-1289 was 90-fold more potent than the precursor LASSBio-897 in aorta from SHR. 20 Many factors are involved in the task of describing the relationship between chemical structure and pharmacological activity of a new drug prototype. Among these factors, the study of atomic-level structure can be included.…”
Section: Introductionmentioning
confidence: 99%